Intron-Based Single Transcript Unit CRISPR Systems for Plant Genome Editing - Zhong, Zhaohui (Rice (N Y), 2020)
BACKGROUND: Expression of either Cas9 or Cas12a and guide RNAs by a single Polymerase II (Pol II) promoter represents a compact CRISPR expression system and has many advantages for different applications. In order to make this system routine in plant biology, engineering efforts are needed for developing and optimizing such single transcript unit (STU) systems for plant genome editing. RESULTS: To develop novel intron-based STU (iSTU) CRISPR system (STU CRISPR 3.0), we first evaluated three introns from three plant species for carrying guide RNAs by using an enhanced green fluorescence protein (eGFP) system in rice. After validation of proper intron slicing, we inserted these gRNA-containing introns into the open reading frames (ORFs) of Cas9 and Cas12a for testing their genome editing capability. Different guide RNA processing strategies have been tested for Cas9 and Cas12a. We demonstrated singular genome editing and multiplexed genome editing with these iSTU-Cas9 and iSTU-Cas12a systems. CONCLUSION: We developed multiple iSTU-CRISPR/Cas9 and Cas12a systems for plant genome editing. Our results shed light on potential directions for further improvement of the iSTU systems.